Long-term haplodeficency of DSPP causes temporomandibular joint osteoarthritis in mice - Qilin Liu; Yitong Zhao; Haibo Shi; Danwei Xiang; Chunye Wu; Lina Song; Ning Ma; Hongchen Sun (BMC, 2024)
Abstract Background Extracellular matrix (ECM) protein malfunction or defect may lead to temporomandibular joint osteoarthritis (TMJ OA). Dentin sialophophoprotein (DSPP) is a mandibular condylar cartilage ECM protein, and its deletion impacted cell proliferation and other extracellular matrix alterations of postnatal condylar cartilage. However, it remains unclear if long-term loss of function of DSPP leads to TMJ OA. The study aimed to test the hypothesis that long-term haploinsufficiency of DSPP causes TMJ OA. Materials and methods To determine whether Dspp +/- mice exhibit TMJ OA but no severe tooth defects, mandibles of wild-type (WT), Dspp +/-, and Dspp homozygous (Dspp −/− ) mice were analyzed by Micro-computed tomography (micro-CT). To characterize the progression and possible mechanisms of osteoarthritic degeneration over time in Dspp +/- mice over time, condyles of Dspp +/- and WT mice were analyzed radiologically, histologically, and immunohistochemically. Results Micro-CT and histomorphometric analyses revealed that Dspp +/- and Dspp −/− mice had significantly lower subchondral bone mass, bone volume fraction, bone mineral density, and trabecular thickness compared to WT mice at 12 months. Interestingly, in contrast to Dspp −/− mice which exhibited tooth loss, Dspp +/- mice had minor tooth defects. RNA sequencing data showed that haplodeficency of DSPP affects the biological process of ossification and osteoclast differentiation. Additionally, histological analysis showed that Dspp +/- mice had condylar cartilage fissures, reduced cartilage thickness, decreased articular cell numbers and severe subchondral bone cavities, and with signs that were exaggerated with age. Radiographic data showed an increase in subchondral osteoporosis up to 18 months and osteophyte formation at 21 months. Moreover, Dspp +/- mice showed increased distribution of osteoclasts in the subchondral bone and increased expression of MMP2, IL-6, FN-1, and TLR4 in the mandibular condylar cartilage. Conclusions Dspp +/- mice exhibit TMJ OA in a time-dependent manner, with lesions in the mandibular condyle attributed to hypomineralization of subchondral bone and breakdown of the mandibular condylar cartilage, accompanied by upregulation of inflammatory markers.